The Impact of the Daily Mile™ on School Pupils’ Fitness, Cognition, and Wellbeing: Findings From Longer Term Participation - Booth, Josephine N.; Chesham, Ross A.; Brooks, Naomi E.; Gorely, Trish; Moran, Colin N. (Frontiers in Psychology, 2022)
Background School based running programmes, such as The Daily MileTM, positively impacts on pupils’ physical health, however, there is limited evidence on psychological health. Additionally, current evidence is mostly limited to examining the acute impact. The present study examined the longer term impact of running programmes on pupil cognition, wellbeing, and fitness. Method Data from 6908 school pupils (mean age 10.2 ± 0.7 years), who were participating in a citizen science project, was examined. Class teachers provided information about participation in school based running programmes. Participants completed computer-based tasks of inhibition, verbal and visual-spatial working memory, as well as the Children’s Feeling scale and Felt arousal scale to determine subjective wellbeing. A multistage 20-m shuttle run test was used to estimate fitness. Results From our total sample of 6908 school pupils, 474 participants had been taking part in a running programme for <2 months (Shorter term participation); 1004 participants had Longer Term participation (>3 months); and 5430 did not take part in a running programme. The Longer Term participation group had higher fitness levels than both other groups and this remained significant when adjusted for age, sex and SES. Moderated regression analysis found that for the Shorter Term participation group, higher shuttle distance was associated with better visual-spatial working memory. Effect sizes were small though. Conclusions We identified small and selective positive impact of participation in school based running programmes on fitness and cognition. While no long term benefit was identified for cognition or wellbeing, the impact on fitness and short term benefit suggest schools should consider participation.